RIBBONFISH FISHERY OF KAKINADA AREA DURING 1977-80 - Sastry, Y Appanna (Indian Journal of Fisheries, 2011)
Annual landings qf ribbonfish at Kakinada by small commercial trawlers varied from 787 t to 2,?23 t during 1977-80 forming on an average 10.5% of the all-fish catch. Catch trends and length-frequency distribution of six species of ribbonfish, namely, frichiurus lepturus, T. susselU, Lepturacanthus gangeticus, L. savala, Eupleutogrammus muticus and E. glossodon are dealt with. Seasonfil fishing trends and the age composition in the landings of T. lepturus, the most dominant specjies, are discussed. A brief account of the ribbonfish fishery by these indigenotjis gears, for the year 1980, at Uppada, a major landing centre near Kakinada, is:also given.